MISTAKEN IDENTITY OF THE VICTIM IN CRIMINAL LAW - Shannon Hoctor (Obiter, 2021)
Along with the drama and pathos that the trial of Oscar Pistorius brought to a multitude of South Africans, who devotedly followed the events (and dissections of events) with great dedication a few years ago, the case also highlighted and publicized a number of legal rules and doctrines. Who would have thought, for example, that the term of art dolus eventualis would emerge as the subject of such quizzical interest for so many? Other issues which emerged are no less interesting from a legal perspective, but are admittedly of much more narrow and parochial interest, being limited to those who are required to apply substantive criminal law, whether in the courts or in the classroom. One of these is the error in obiecto notion (the spelling “obiecto”, rather than “objecto” which more typically appears in the textbooks and the case law, is more correct, although, both spelling forms will be used below, as needs be). The word “notion” is carefully selected, since describing error in obiecto as a rule, has been firmly and correctly dismissed as incorrect by Snyman (Hoctor Snyman’s Criminal Law 7ed (2020) 171): “[It] is not the description of a legal rule; it merely describes a certain type of factual situation.” Burchell’s point of departure is even more stark: “[T]he so-called error in objecto rule has uncertain, dubious origins and reference to it, even as a description of a factual predicament, should be excluded from the lawyers’ lexicon”. Phelps uses the phrase “little-known principle” to describe this “factual predicament”. The author in Kemp, Walker, Palmer, Baqwa, Gevers, Leslie and Steynberg Criminal Law in South Africa 3ed (2018) 263 does not use any nomenclature when discussing the legal position arising out of this factual situation.